Problemas ergonômicos enfrentados por profissionais de enfermagem em ambientes hospitalares: aspectos da interface trabalhadores x equipamentos - Rodrigues, Leandro Henrique [UNESP]; Barela, Jefferson [UNESP]; Costa, Willian Barela [UNESP]; Paschoarelli, Luís Carlos [UNESP]; Silva, José Carlos Plácido da [UNESP] (My University, 2013)
The ergonomic design seeks to establish parameters to improve the interface between the technologies (products, systems and environments) and between man (users). Among the many factors involved, there are the activities performed in hospital settings, both by patients and by clinical staff. Accordingly, efforts have been demonstrated biomechanical with a leading occupational problem, especially regarding the transfer of patients.

O design ergonômico busca estabelecer parâmetros para aprimorar a interface entre as tecnologias (produtos, ambientes e sistemas) e entre o homem (usuários). Entre os inúmeros fatores envolvidos, destacam -se as atividades realizadas em ambientes hospitalares, tanto por pacientes quanto pela equipe clínica. Nesse sentido, os esforços biomecânicos têm se demonstrado com um dos principais problemas ocupacionais, especialmente referente à transferência de pacientes.
Ergonomic problems faced by nursing professionals in hospitals: aspects of the interface workers work equipment
Keywords: Ergonomics; Ergonomic design; Nursing; Ergonomia; Design ergonômico; Enfermagem